The $100 startup : reinvent the way you make a living, do what you love, and create a new future - Guillebeau, Chris (New York : Crown Business, 2012)
Here, Chris Guillebeau shows you how to lead a life of adventure, meaning and purpose--and earn a good living. Still in his early thirties, Chris has traveled around the world--and yet he's never held a'real job' or earned a regular paycheck. Rather, he has a genius for turning ideas into income, and he uses what he earns both to support his life of adventure and to give back. In preparing to write this book, Chris identified 1,500 individuals who have built businesses earning $50,000 or more from a modest investment, and he's focused on the 50 most intriguing case studies. Here, distilled into one easy-to-use guide, are the most valuable lessons from those who've learned how to turn what they do into a gateway to self-fulfillment. It's all about finding the intersection between your expertise and what other people will pay for. You don't need an MBA, a business plan or even employees. All you need is a product or service that springs from what you love to do anyway, people willing to pay, and a way to get paid.--From publisher description.
Prologue: Manifesto: a short guide to everything you want -- Pt. 1: Unexpected entrepreneurs. Renaissance : you already have the skills you need--you just have to know where to look ; Give them the fish : how to put happiness in a box and sell it ; Follow your passion--maybe : get paid to do what you love by making sure it connects to what other people want ; The rise of the roaming entrepreneur :'location, location, location' is overrated ; The new demographics : your customers all have something in common, but it has nothing to do with old-school categories -- Pt. 2: Taking it to the streets. The one- page business plan : if your mission statement is much longer than this sentence, it could be too long ; An offer you can't refuse : the step-by-step guide to creating a killer offer ; Launch! A trip to Hollywood from your living room or the corner coffee shop ; Hustling : the gentle art of self-promotion : advertising is like sex-- only losers pay for it ; Show me the money : unconventional fundraising from Kickstarter to unlikely car loans -- Pt. 3: Leverage and next steps. Moving on up : tweaking your way to the bank : how small actions create big increases in income ; How to franchise yourself : instructions on cloning yourself for fun and profit ; Going long : become as big as you want to be (and no bigger) ; But what if I fail? How to succeed even if your roof caves in on you.
Includes index.
Keywords: New business enterprises -- Management; Entrepreneurship